About Ciliates Entodinium palmare and E. okoppensis (Ciliophora: Ophryoscolecidae) in the Rumen of Domestic Cattles (Bos taurus taurus) in the vicinity of Kastamonu - Gürelli, Gözde (Galenos Yayinevi, 2013)
The aim of this study was to determine the cytological features of the rumen ciliates Entodinium palmare and E. okoppensis living in the rumen of domestic cattle in the vicinity of Kastamonu, compare the morphological characters of species with their original descriptions and discuss the similarities and differences.The specimens were obtained from 24 cattle, fixed with 10% formalin and stained with methylgreen formalin saline (MFS) solution.Specimens were measured from cattle in our country, and were found to be similar to the original description on the basis of morphological characteristics and biometric data.With this investigation, E. palmare and E. okoppensis were firstly detected from our cattle and were secondly detected from cattle throughout the world. E. palmare and E. okoppensis have low frequency appearance and percentage composition in our cattle. This study concluded that the feeding habits and feeding frequencies of cattle, the physiological conditions of rumen or competition between species can be important reasons for this situation.
Keywords: Biometry; Rumen; Stomach Diseases; Animals; Cattle Diseases; Cattle; Ciliophora Infections; Ciliophora; 2. Zero hunger